Advances in cancer research. - Vande Woude, George F.; Klein, George, 1925-2016 (Advances in cancer research, 1995)
ADVANCES IN CANCER RESEARCH is a biannual publication that includes timely reviews on the most cutting-edge issues in cancer research. Volume 66 contains encompassing overviews of p53 and its role in both breast cancer and in the cell cycle. Approximately 50% of all human tumors involve mutations of the p53 gene, suggesting that proper understanding of its properties and mechanisms could offer real hope for finding successful clinical therapy. Other themes presented in Volume 66 include cyclins and cyclin-dependant kinases in the cell cycle: the molecular genetics of 11q23 chromosome translocations: the possible link between the aberrant expression of Scatter Factor and c-Met with AIDS Associated kaposi's Sarcoma, the use of Radiation Leukemia Virus to induce leukemogenesis, and the Adenovirus system as a model for the insertion of foreign DNA into mammalian genomes. Also of note in the "Foundations of cancer Research" section are articles by two prominent cancer researchers recollecting the ideas and paths taken in their lifelong work. Paradigms proposed in these reviews mark thoughtful progress toward preventative therapy in oncogenesis and gene therapy of cancer. They also cast light on the fact that the ideas presented in these chapters are only the tip of the iceberg in this complex and ever evolving field, and suggest many more to come in future volumes. Key Features * Contains two Foundations in Cancer Research articles with personal accounts by prominent biologists on their careers in cancer research * Presents overviews of the role of p53 in breast cancer and cell cycle regulation * Describes the regulatory role of cyclins and cyclin dependent kinases in DNA replication and cell division * Explains the puzzling link between HIV infection and Kaposis Sarcoma * Includes models for retrovirus-induced tumorigenesis and foreign DNA insertion into mammalian genomes.